Highly active bimetallic noble metal alloys electrocatalyst - Ong, Su-Ann (Nanyang Technological University, 2022)
As Hydrogen fuel is looking to be a strong contender for an alternative source of fuel in the future, an efficient catalyst has to be found to aid in the water splitting process. In this report, thin film electrocatalysts of Rh, Rh-Pt and Rh-Ir were fabricated by using Atomic Layer Deposition (ALD) on a glassy carbon (GCE) substrate.